2019
DOI: 10.3390/info10120383
|View full text |Cite
|
Sign up to set email alerts
|

Container Terminal Logistics Generalized Computing Architecture and Green Initiative Computational Pattern Performance Evaluation

Abstract: Container terminals are the typical representatives of complex supply chain logistics hubs with multiple compound attributes and multiple coupling constraints, and their operations are provided with the strong characteristics of dynamicity, nonlinearity, coupling, and complexity (DNCC). From the perspective of computational logistics, we propose the container terminal logistics generalized computing architecture (CTL-GCA) by the migration, integration, and fusion of the abstract hierarchy, design philosophy, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Moreover, the authors of reference [36] simulated the indoor air quality of roll-on/ roll-of (RORO) ships and predicted pollution emitted from cars in maritime ports. Furthermore, the authors of reference [37] developed a container terminal logistics generalized computing architecture (CTL-GCA) for planning, scheduling and decision making to establish a better connection among liners and rubber-tired gantry cranes (RTGCs) and block community to reduce carbon emissions.…”
Section: Overall Port Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the authors of reference [36] simulated the indoor air quality of roll-on/ roll-of (RORO) ships and predicted pollution emitted from cars in maritime ports. Furthermore, the authors of reference [37] developed a container terminal logistics generalized computing architecture (CTL-GCA) for planning, scheduling and decision making to establish a better connection among liners and rubber-tired gantry cranes (RTGCs) and block community to reduce carbon emissions.…”
Section: Overall Port Areasmentioning
confidence: 99%
“…Te authors showed the beneft of container clustering in terms of reducing the number of trucks for moving the same number of containers. In the same area, the authors of reference [37] developed a k-means model based on the number of RTGs, blocks, handling container specifcations, stevedoring full or empty category, handling volume for a task, and the number of clusters to manage the relationship between RTG crane teams and the given block sets. Te authors concluded that the k-means model was an efcient tool for clustering block communities and dispatching RTG cranes in the yard area.…”
Section: Unsupervised Learningmentioning
confidence: 99%
“…ere are 13,873 container vessels for the domestic trade to visit the terminal during this period. It is a physically demanding job set for CTO-LGC for the six years to execute the quantitative random job testing for CTHS [73]. e preliminary sketch of LHV can be illustrated by Figure 3 and Table 1, and two distinct features are shown in both.…”
Section: Case Scenario and Loading Job Set Evaluationmentioning
confidence: 99%